Social Exclusion and the Criminal Justice System: A Comparative Analysis. - García-España, Elisa; Cerezo-Domínguez, Ana Isabel; Pérez-Jiménez, María Fátima; Güerri-Ferrández, Cristina; Arenas-García, Lorea; Díez-Ripollés, José Luis; Becerra-Muñoz, José; Contreras-Román, María; Corral, Noelia; Rando Casermeiro, Pablo; Prado-Manrique, Bertha; Casado Patricio, Elena; et al. (Routledge, 2024)
This book presents the results of the latest in a long-running research project using the RIMES instrument, developed by scholars in Spain. Here, RIMES is used to measure the extent of social exclusion resulting from the penal system in comparative perspective. The volume shows the results of the application of the instrument in seven criminal justice systems: Germany, Italy, Spain, Poland, England and Wales, California, and New York. Divided into two parts, the first provides a general overview of the RIMES instrument, including a discussion of the theoretical model and the methodology. The second part focuses on the results of the application of RIMES in the seven jurisdictions. The comparative results are organised according to the nine dimensions included in the RIMES instrument: control of public spaces; legal safeguards; sentencing and sanctions systems; harshest penalties; prison rules; preventive intervention; legal and social status of offenders and ex-offenders; police and criminal records; and youth criminal justice. The last chapter summarizes the comparative results and ranks them in terms of the findings on social exclusion. The book will be of interest to academics, researchers and policy-makers working in the areas of Comparative Criminal Justice, Criminology, Criminal Law and Policy.
Keywords: Exclusión social; Política criminal; RIMES; Criminal policy; Comparative analysis; Social exclusion